(untitled) (Samsad Journal संसद जर्नल, 2025)
This article analyzes Nepal’s macroeconomic developments in the post-COVID 19 context, emphasizing key trends, emerging imbalances, and policy challenges. While the economy demonstrated resilience through a rapid recovery in GDP growth, it simultaneously encountered inflationary pressures, external sector stress, and rising fiscal deficits. The paper explores the structural roots of macroeconomic imbalances, such as expansionary monetary policies, excessive liquidity, growing public debt, and the current account deficit. It also contrasts Nepal’s performance with South Asian neighbors and outlines actionable policy recommendations. These include fiscal and monetary reforms, better macroeconomic coordination, and the need for a second-generation economic reform agenda to ensure long-term stability and inclusive growth.